Theoretical Analysis of Plasmon-Induced Transparency in MIM Waveguide Bragg Grating Coupled With a Single Subradiant Resonator - Xin Luo; Xiang Zhai; Lingling Wang; Qi Lin; Jianping Liu (IEEE Photonics Journal)
A plasmon-induced transparency (PIT) spectral response in an ultracompact plasmonic structure composed of a metal–insulator–metal waveguide Bragg grating coupled with an air rectangle cavity is proposed, and the corresponding transmission characteristics are investigated theoretically and numerically. By using the transmission line theory (TLT), a remarkable PIT transmission can be proposed in this structure. Moreover, we study the transmission as a function of the coupling distance between the air cavity and insulator layer, and we also discuss the transmission as a function of the thickness of air cavity. To validate the correctness of the TLT results, we have compared them with the finite-difference time-domain method. Both of them agree well with each other. Thus, our results can offer a new possibility and important theory analysis for the designs of the optical switching devices, sensors, and slow light devices in highly integrated optical circuits.